PH response type adsorbent as well as preparation method and application thereof
By developing pH-responsive adsorbents, using their selective adsorption ability under acid and alkaline changes, the performance and stability of adsorbents under environmental changes are solved, and a wider application and more efficient adsorption separation effect is achieved. .
Patent Information
- Application Number
- CN202411753819.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-18
AI Technical Summary
When the external environment changes, the adsorption performance and stability of existing adsorbents are seriously affected, limiting their application potential.
A pH-responsive adsorbent is developed to enhance the surface hydrophilicity and number of adsorbent sites by synthesizing adsorbents with layered porous structures and forming dual adsorbent sites after acid activation.
It realizes selective adsorption and separation of different ions under different pH environments, adapts to the acid-base changes of the solution, maintains stability, broadens the application occasions and conditions of adsorbents, and improves the ability of adsorption separation and resource utilization.
Smart Images

Figure CN119455903A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an adsorbent and a preparation method and application thereof, and in particular to a pH-responsive adsorbent and a preparation method and application thereof, belonging to the field of adsorbent preparation. Background Art
[0002] Adsorption has received extensive attention and systematic research due to its excellent separation performance, simple operation process and low operating costs. At present, adsorption is mainly used in the extraction and separation of ions, separation and storage of gases, and removal of water pollutants. However, different fields have their own application conditions and goals, which puts higher requirements on the development of adsorbents. Not only the physical and chemical properties of the adsorbent should be considered, but also the adsorption performance, stability and adaptability of the adsorbent itself to the application conditions should be measured.
[0003] In addition, for the same adsorbent, changes in the external environment have a serious impact on its adsorption performance and its own stability, which greatly limits the application potential of the adsorbent. Therefore, it is very important to develop a multi-purpose and multifunctional adsorbent.
[0004] The development of adsorbents mainly revolves around the physical and chemical properties of materials. The physical properties of materials include specific surface area, pore size, pore distribution, surface hydrophilicity / hydrophobicity, etc. These properties mainly affect the diffusion process of guest molecules and the contact process with adsorption sites. These physical properties are adjustable properties, and the physical properties of materials can be changed according to production needs to achieve the desired goals. The chemical properties of materials are an intrinsic property of the material itself, which determines the application scope and application potential of the material.
[0005] In addition, it is difficult to change the chemical properties of materials, which places high demands on the materials themselves and the synthesis process. However, the chemical properties of materials not only affect the application potential and scope of the materials, but also influence the physical properties of the materials to a certain extent.
[0006] Therefore, appropriate regulation of the physical and chemical properties of the material can not only meet the needs of improving existing functions, but also obtain new properties, providing the possibility for the preparation of multifunctional adsorbents. Summary of the invention
[0007] In view of this, the present invention provides a pH-responsive adsorbent and its preparation method and application, which can efficiently capture copper ions in an acidic solution and has a high separation performance for lithium ions and iron ions; when the adsorbent is in an alkaline solution, it can efficiently capture lithium ions in the solution and has a certain separation ability for sodium ions and potassium ions. Therefore, the present invention helps to achieve the selective adsorption and separation of different ions under different pH environments.
[0008] In order to achieve the above object, one of the technical solutions of the present invention is a method for preparing a pH-responsive adsorbent, comprising the following steps:
[0009] S1. dissolving aluminum nitrate nonahydrate in ultrapure water, and then mixing with 1,2,4,5-benzenetetracarboxylic acid to heat and react to generate a white solid;
[0010] S2, washing the white solid with anhydrous ethanol by centrifugation, and then soaking it in anhydrous methanol after ultrasonic mixing;
[0011] S3, centrifuging the soaked solid, and then activating it by vacuum drying to obtain MIL-121;
[0012] S4, MIL-121 is mixed with lithium hydroxide solution, reacted in an ice water bath, and after the reaction, the solid is centrifuged and dried to obtain CAOMIL
[0013] S5. Activate CAOMIL with dilute hydrochloric acid solution to obtain H-CAOMIL, centrifuge, wash with methanol by centrifugation, and then dry in vacuum.
[0014] On the basis of the above technical solution, the present invention further defines the solution as follows:
[0015] Further, in step S1, the molar ratio of aluminum nitrate nonahydrate to 1,2,4,5-benzenetetracarboxylic acid is 13:6;
[0016] The reaction temperature was 150°C and the reaction time was 48h.
[0017] Furthermore, the centrifugal washing condition in step S2 is 7000-8000 r / min, the number of centrifugal washing is three times, and the soaking time is 12 hours.
[0018] Furthermore, in step S3, the centrifugal condition is 8000 r / min, the vacuum drying temperature is 120° C., and the drying time is 12 h.
[0019] Further, the concentration of the lithium hydroxide solution in step S4 is 0.1 mol / L, and the amount used is 5-30 mL of lithium hydroxide solution per gram of MIL-121;
[0020] The reaction time is 1 hour, the centrifugal parameters are 5000-6000 r / min, and the drying temperature is 60°C.
[0021] Further, in step S5, the concentration of dilute hydrochloric acid is 0.1 mol / L;
[0022] The shaking parameters were 45°C, 170 r / min, the activation time was 10 h, the parameters for the centrifugal washing with methanol were 8000 r / min, the number of centrifugal washings was three times, and the temperature of the vacuum drying was 120°C, and the time was 12 h.
[0023] The beneficial effect of adopting the above technical solution is that the adsorbent with a hierarchical porous structure is directly synthesized by in-situ conversion, and after acid activation, not only dual adsorption sites are formed, but also the surface properties of the adsorbent are further improved. In addition, the increase in the content of free carboxyl groups on the surface of the adsorbent not only enhances the hydrophilicity of the material surface, which is conducive to ion diffusion, but also increases the number of adsorption sites and strengthens the adsorption process.
[0024] Another technical solution of the present invention is a pH-responsive adsorbent prepared by the above method.
[0025] Another technical solution of the present invention is the use of the above-mentioned pH-responsive adsorbent to adsorb copper ions in an acidic solution and desorb copper ions in a weakly acidic solution to obtain a solution containing copper ions and / or to adsorb lithium ions in an alkaline solution and desorb lithium ions in a weakly acidic solution to obtain a solution containing lithium ions.
[0026] Among them, in the adsorption of copper ions, the pH of the acidic solution is 3-7, the adsorption temperature is 45°C, the adsorption liquid-solid ratio is 40mL / g, the adsorption time is 24h, and the adsorption speed is 170r / min;
[0027] In the desorption of copper ions, the weak acid solution was a 0.05 mol / L dilute nitric acid solution, the desorption temperature was 45 °C, the desorption liquid-solid ratio was 120 mL / g, the desorption time was 9 h, and the desorption speed was 170 r / min;
[0028] In the adsorption of lithium ions, the pH of the alkaline solution was 7-12, the adsorption temperature was 30°C, the adsorption liquid-solid ratio was 100 mL / g, the adsorption time was 40 minutes, and the adsorption speed was 170 r / min;
[0029] In the desorption of lithium ions, the weakly acidic solution is a 0.1 mol / L dilute hydrochloric acid solution, the desorption temperature is 30°C, the desorption liquid-solid ratio is 100 mL / g, the desorption time is 7 h, and the desorption speed is 170 r / min.
[0030] The beneficial effect of adopting the above technical solution is that the adsorbent can not only adapt to the changes in the acidity and alkalinity of the solution and maintain a certain stability, but also realize the selective adsorption and separation of different ions in different environments. The emergence of these new properties can not only broaden the application occasions and application conditions of the adsorbent, but also further enhance the adsorbent's ability in adsorption, separation and resource utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Quantitative characterization of defects under different preparation conditions (AAS and XRD);
[0032] Figure 2 is the lithium ion adsorption performance under different defect levels;
[0033] Figure 3 XRD patterns of the hydrothermally synthesized metal-organic framework MIL-121, H-CAOMIL;
[0034] Figure 4 SEM images of the hydrothermally synthesized metal-organic framework MIL-121, H-CAOMIL;
[0035] Figure 5 FTIR images of the hydrothermally synthesized metal-organic framework MIL-121, H-CAOMIL;
[0036] Figure 6 XPS images of the hydrothermally synthesized metal-organic framework MIL-121, H-CAOMIL;
[0037] Figure 7 is the XRD pattern of H-CAOMIL after cycling in acidic adsorption solution and alkaline adsorption solution; DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] The preparation method of pH responsive adsorbent comprises the following steps:
[0041] (1) 4.8 g of aluminum nitrate nonahydrate was dissolved in 20 mL of ultrapure water to form a colorless and transparent solution, and then 1.6 g of 1,2,4,5-benzenetetracarboxylic acid was added to the solution and ultrasonically mixed, and then the mixed suspension was transferred to a hydrothermal reactor and reacted in an oven at 150°C for 48 hours; after the reaction was completed and the reactor was cooled to room temperature, the product was centrifuged and washed three times with anhydrous ethanol, and then soaked in anhydrous methanol overnight; after the soaking was completed, the reactants were centrifuged and activated in a vacuum oven at 120°C for 12 hours to obtain a white metal organic framework MIL-121.
[0042] Its X-ray diffraction pattern, scanning electron microscope image, Fourier transform infrared spectrum and X-ray photoelectron spectrum are as follows: Figure 1-3 shown.
[0043] (2) 1 g of the MIL-121 synthesized in (1) was added to 0, 5, 10, 20, and 30 mL of 0.1 mol / L lithium hydroxide solution, respectively, and reacted in an ice-water bath for 1 h. The resulting samples were labeled D0, D1, D2, D3, and D4, respectively. The reaction product was centrifuged, washed three times with anhydrous ethanol, and dried in an oven at 60°C. 1.8 g of the dried sample was added to 180 mL of dilute hydrochloric acid solution and subjected to an acid activation experiment in a constant temperature shaker at 45°C for 10 h. After the acid activation, the adsorbent was centrifuged, washed with ultrapure water until the washing liquid was neutral, washed three times with anhydrous ethanol, and finally soaked in anhydrous methanol for about 12 h. After the soaking, it was centrifuged and dried in a vacuum oven at 120°C for 12 h.
[0044] Defect quantification experiments and characterizations were conducted on the above-mentioned D0, D1, D2, D3, and D4 adsorbents. The quantification experimental process is as follows: an atomic absorption spectrophotometer (AAS) was used to test the reduction of lithium ions in the LiOH solution, and the adsorption capacity and structure characterization of each sample after acid activation and vacuum activation were tested to further determine the optimal synthesis conditions. The quantitative experimental results are shown in FIG. Figure 1-2 The X-ray diffraction pattern, scanning electron microscope image, Fourier transform infrared spectrum and X-ray photoelectron spectrum of the sample under the optimal synthesis conditions are shown in Figure 3-6 shown.
[0045] according to Figure 1-3 It can be seen that H-CAOMIL inherits the crystal structure of MIL-121, but H-CAOMIL has greater advantages than MIL-121 in terms of physical and chemical properties; in terms of physical properties, H-CAOMIL has a larger specific surface area, richer pore distribution and higher surface hydrophilicity. In terms of chemical properties, H-CAOMIL not only has good thermal stability, but also has a large number of exposed Al-OH adsorption sites and free carboxyl (R-COOH) adsorption sites.
[0046] Example 2
[0047] Copper ion extraction efficiency test under acidic conditions:
[0048] The adsorbent synthesized in Example 1 was used for copper ion extraction experiments under acidic conditions (pH=5.35 and pH=4.25). The adsorption experiments were carried out in a constant temperature shaker, with the shaker speed set to 170r / min, the temperature set to 45°C, and the time gradient settings being: 1, 3, 6, 10, 24 hours and 1, 3, 7, 12, 24 hours. The copper ion concentrations in the acidic solution were 352mg / L and 356mg / L, respectively, and the adsorption liquid-solid ratios were set to 40mL / g and 60mL / g, respectively.
[0049] The adsorption results are shown in Tables 1 and 2.
[0050] Table 1 Cu adsorbent in solution with pH = 5.35 2+ Adsorption capacity
[0051]
[0052] Table 2 Cu adsorbent in solution with pH = 4.25 2+ Adsorption capacity
[0053]
[0054] Example 3
[0055] Effect of temperature on the adsorption of copper ions under acidic conditions:
[0056] The adsorbent synthesized in Example 1 was used for a copper ion adsorption experiment under acidic conditions (pH = 5.74). The adsorption experiment was carried out in a constant temperature shaker, the shaker speed was set to 170 r / min, the temperature was set to 25°C, 35°C, and 45°C, the adsorption time was set to 24 h, the adsorption liquid-solid ratio was set to 40 mL / g, and the initial concentration of copper ions was 395 mg / L.
[0057] The adsorption results are shown in Table 3.
[0058] Table 3 Effect of temperature on adsorption capacity of adsorbent
[0059]
[0060] Example 4
[0061] Thermodynamics of copper ion adsorption:
[0062] The adsorbent synthesized in Example 1 was used in a copper ion adsorption thermodynamic experiment under acidic conditions (pH = 6.14). The adsorption temperatures (Kelvin temperatures) were set to 298.15, 308.15, 318.15, and 328.15 K, the adsorption time was set to 24 h, the adsorption liquid-solid ratio was set to 80 mL / g, and the initial copper ion concentration was (507 mg / L). The distribution coefficient (Kd), thermodynamic constant (K), entropy change (ΔS), enthalpy change (ΔH), and Gibbs free energy change (ΔG) during the adsorption of copper ions by the adsorbent were investigated in detail.
[0063] Thermodynamic data are shown in Table 4.
[0064] Table 4 Thermodynamic data of adsorbent adsorption of copper ions
[0065]
[0066] Example 5
[0067] Adsorption cycle stability of copper ions adsorbed by adsorbent:
[0068] The adsorbent synthesized in Example 1 was used in a copper ion adsorption cycle experiment under acidic conditions (pH = 6.14), the adsorption temperature was set to 45 ° C, the adsorption liquid-solid ratio was set to 40 mL / g, the adsorption time was set to 24h, the shaking table speed was set to 170r / min, the number of adsorption cycles was set to 15 times, and the adsorption conditions were consistent for each cycle.
[0069] The results of the number of cycles and adsorption capacity are shown in Table 5. Figure 5 , Figure 7 shown.
[0070] Table 5 Relationship between adsorption capacity and adsorption cycle number
[0071] Cycle times Temperature(℃) Adsorption liquid-solid ratio Time (h) Adsorption capacity (mg / g) 1 45 40 24 18.2 2 45 40 24 18.15 3 45 40 24 18 4 45 40 24 16.4 5 45 40 24 17.8 6 45 40 24 19 7 45 40 24 16 8 45 40 24 17.1 9 45 40 24 17.4 10 45 40 24 17.9 11 45 40 24 16.9 12 45 40 24 15.8 13 45 40 24 16 14 45 40 24 15.5 15 45 40 24 15.4
[0072] Example 6
[0073] Desorption performance of copper ions:
[0074] The desorption test was carried out using the adsorbent after adsorbing copper ions in Example 2 as the desorption sample, the desorption temperature was set to 45°C, the desorption time was set to 1, 2, 4, 6, and 8 h, the desorption liquid-solid ratio was set to 100 mL / g, the desorption liquid was 0.05 mol / L nitric acid solution, and the desorption process was carried out in a constant temperature shaker at a speed of 170 r / min.
[0075] The desorption results are shown in Table 6.
[0076] Table 6 Copper ion desorption and desorption rate test
[0077]
[0078] It can be seen from Tables 1, 2, 3, 5, and 6 that the pH-responsive adsorbent H-CAOMIL has a high copper ion adsorption capacity (18.2 mg / g) in acidic copper-containing solutions, and can effectively capture copper ions in solutions of different acidity, and has a wide range of applications. In addition, the pH-responsive adsorbent has excellent copper ion desorption performance, can desorb copper ions in a relatively short period of time, and achieves regeneration of the adsorbent, and the regenerated adsorbent has high stability. Ten consecutive adsorption and desorption cycles have proved that the adsorption capacity of H-CAOMIL can be maintained at about 98%, and has high stability.
[0079] Example 7
[0080] Lithium ion extraction test under alkaline conditions:
[0081] The adsorbent synthesized in Example 1 was used for lithium ion adsorption experiments under alkaline conditions, with the pH set to 7, 9, 10, 11, and 12, the adsorption temperature set to 30° C., the adsorption time set to 1 h, the initial lithium ion concentration in the adsorption solution set to 600 mg / L, and the adsorption liquid-solid ratio set to 50 mL / g.
[0082] The adsorption results are shown in Table 7.
[0083] Table 7 Lithium ion adsorption under alkaline conditions
[0084]
[0085] Example 8
[0086] Time observation on lithium ion extraction:
[0087] The adsorbent synthesized in Example 1 was used for lithium ion adsorption experiments under alkaline conditions, with the adsorption pH set to 12, the adsorption temperature set to 30°C, the adsorption liquid-solid ratio set to 50 mL / g, the adsorption time set to 0, 10, 20, 40, and 60 minutes, and the initial lithium ion concentration of the adsorption liquid set to 100 mg / L.
[0088] The adsorption results are shown in Table 8.
[0089] Table 8 Investigation of the effect of adsorption time on lithium ion adsorption under alkaline conditions
[0090]
[0091] Example 9
[0092] Study on the effect of temperature on lithium ion adsorption performance
[0093] The adsorbent synthesized in Example 1 was used for lithium ion adsorption experiments under alkaline conditions, with the temperature set to 20, 30, 40, and 50° C., the pH set to 12, the liquid-solid ratio set to 50 mL / g, and the initial lithium ion concentration set to 100 mg / L.
[0094] The adsorption results are shown in Table 9.
[0095] Table 9 Study on the effect of temperature on lithium ion adsorption
[0096]
[0097] Example 10
[0098] Investigation of lithium ion adsorption thermodynamics under alkaline conditions:
[0099] The adsorbent synthesized in Example 1 was used to investigate the thermodynamics of lithium ion adsorption under alkaline conditions, with the temperature gradient set to 293, 303, 313, and 323 K (temperature is Kelvin temperature), the adsorption time set to 1 h, the adsorption liquid-solid ratio set to 50 mL / g, and the initial lithium ion concentration set to 100 mg / L.
[0100] The corresponding thermodynamic parameters are shown in Table 10.
[0101] Table 10 Thermodynamics of lithium ion adsorption under alkaline conditions
[0102]
[0103] Embodiment 11
[0104] Cyclic stability of lithium ion adsorption under alkaline conditions:
[0105] The adsorbent synthesized in Example 1 was used to investigate the lithium ion adsorption cycle stability under alkaline conditions, with the adsorption temperature set to 30°C, the adsorption liquid-solid ratio set to 80 mL / g, the adsorption time set to 1 h, and the initial lithium ion concentration of the solution set to 100 mg / L.
[0106] The lithium ion adsorption results under different cycle numbers are shown in Table 11 and Figure 7 shown.
[0107] Table 11 Lithium ion adsorption at different cycle times under alkaline conditions
[0108] Cycle times Temperature(℃) Adsorption liquid-solid ratio Time (h) Adsorption capacity (mg / g) 1 30 80 1 5.5 2 30 80 1 5.3 3 30 80 1 5.3 4 30 80 1 4.6 5 30 80 1 5.1
[0109] From Examples 1 to 11, it can be seen that the pH-responsive adsorbent H-CAOMIL has both acid-base properties, which not only maintains structural stability, but also can adsorb and separate different metal ions due to changes in acidity and alkalinity. It can adsorb copper ions under acidic conditions, and has not only high adsorption capacity but also high cycle stability; the same is true under alkaline conditions, and it can maintain its own stability while adsorbing lithium ions. This pH-responsive adsorbent not only has a wider range of applications, but also opens up new ideas for the design of adsorbents.
Claims
1. A method for preparing a pH-responsive adsorbent, characterized in that: The following steps are involved: S1. dissolving aluminum nitrate nonahydrate in ultrapure water, and then mixing with 1,2,4,5-benzenetetracarboxylic acid to heat and react to generate a white solid; S2, washing the white solid with anhydrous ethanol by centrifugation, and then soaking it in anhydrous methanol after ultrasonic mixing; S3, centrifuging the soaked solid, and then activating it by vacuum drying to obtain MIL-121; S4, MIL-121 is mixed with lithium hydroxide solution, reacted in an ice water bath, and after the reaction, the solid is centrifuged and dried to obtain CAOMIL S5. Activate CAOMIL with dilute hydrochloric acid solution to obtain H-CAOMIL, centrifuge, wash with methanol by centrifugation, and then dry in vacuum.
2. The method for preparing the pH-responsive adsorbent according to claim 1, characterized in that: In step S1, the molar ratio of aluminum nitrate nonahydrate to 1,2,4,5-benzenetetracarboxylic acid is 13:6; The reaction temperature was 150°C and the reaction time was 48h.
3. The method for preparing the pH-responsive adsorbent according to claim 1, characterized in that: The centrifugal washing condition in step S2 is 7000-8000 r / min, the number of centrifugal washing is three times, and the soaking time is 12 hours.
4. The method for preparing the pH-responsive adsorbent according to claim 1, characterized in that: In step S3, the centrifugal condition is 8000 r / min, the vacuum drying temperature is 120° C., and the drying time is 12 h.
5. The method for preparing the pH-responsive adsorbent according to claim 1, characterized in that: The concentration of the lithium hydroxide solution in step S4 is 0.1 mol / L, and the amount used is 5-30 mL of lithium hydroxide solution per gram of MIL-121; The reaction time is 1 hour, the centrifugal parameters are 5000-6000 r / min, and the drying temperature is 60°C.
6. The method for preparing the pH-responsive adsorbent according to claim 1, characterized in that: In step S5, the concentration of dilute hydrochloric acid is 0.1 mol / L; The shaking parameters were 45°C, 170 r / min, the activation time was 10 h, the parameters for the centrifugal washing with methanol were 8000 r / min, the number of centrifugal washings was three times, and the temperature of the vacuum drying was 120°C, and the time was 12 h.
7. A pH-responsive adsorbent prepared by the method according to any one of claims 1 to 6.
8. Use of the pH-responsive adsorbent according to claim 7 or the pH-responsive adsorbent prepared by the method according to any one of claims 1 to 6 for adsorbing copper ions in an acidic solution and desorbing copper ions in a weakly acidic solution to obtain a solution containing copper ions and / or for adsorbing lithium ions in an alkaline solution and desorbing lithium ions in a weakly acidic solution to obtain a solution containing lithium ions.
9. The use according to claim 8, characterized in that: In the adsorption of copper ions, the pH of the acidic solution was 3-7, the adsorption temperature was 45°C, the adsorption liquid-solid ratio was 40 mL / g, the adsorption time was 24 h, and the adsorption speed was 170 r / min; In the desorption of copper ions, the weakly acidic solution was a 0.05 mol / L dilute nitric acid solution, the desorption temperature was 45°C, the desorption liquid-solid ratio was 120 mL / g, the desorption time was 9 h, and the desorption speed was 170 r / min.
10. The use according to claim 8, characterized in that: In the adsorption of lithium ions, the pH of the alkaline solution was 7-12, the adsorption temperature was 30°C, the adsorption liquid-solid ratio was 100 mL / g, the adsorption time was 40 minutes, and the adsorption speed was 170 r / min; In the desorption of lithium ions, the weakly acidic solution is a 0.1 mol / L dilute hydrochloric acid solution, the desorption temperature is 30°C, the desorption liquid-solid ratio is 100 mL / g, the desorption time is 7 h, and the desorption speed is 170 r / min.